Rodents As Potential Hosts And Reservoirs Of Parasites Along The Edge Of A Central African Forest: Bwindi Impenetrable National Park, South Western Uganda - Mawanda, Patrick; Rwego, Innocent; Kisakye, John J.; Sheil, Douglas (African Health Sciences, 2020)
Rodents which constitute 42% of the world’s mammalian population are major reservoirs of pathogens that cause zoonoses. Currently we know little about rodents’ potential zoonotic transfer from human settlements into protected areas and how any such threats might be reduced.To investigate the role of rodents as reservoirs of zoonotic pathogens along the boundary of Bwindi.A rodent inventory in three villages along the edge of Bwindi, was carried using live trapping techniques and the local rodents’ ecto and endoparasite fauna investigated.Two hundred eighty eight rodents captured belonged to 24 species, 17 genera and 4 families with Lophuromys aquilus being most abundant (30.2%). 240 ectoparasites which included mites, fleas and ticks were collected from 88 rodents out of 249. Proamys jacksoni rodents were most infested. Although the mites represented the largest proportion (84.6%), the highest species diversity was shown among the fleas (9 species). Some 36.9% of the rodents were infected with endopara- sites of which L. aquilus haboured most. Endoparasitic genera identified included Nippostrongylus, Ascaris, Strongyloides, Trichuris, Hymenolepis, Taenia and Cryptosporidium.Rodents have a zoonotic potentiality. There is need for developing effective integrated rodent management programs against rodent to reduce chances of parasite transmission within the protected areas.
Keywords: Bwind; human disease; mountain gorillas; rodents; transmission.